A PROPOSED HABILITATION PROGRAM TO IMPROVE SOME RESPIRATORY SIGNS USING AQUA-AEROBIC EXERCISES TO REDUCE THE INTENSITY AND SEVERITY OF ASTHMA ATTACKS AMONG CHILDREN - Delimi Omar; Zabchi Nor eddine; Mkrani Djamel (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2020)
The aim of this study was to propose a rehabilitation program using aqua-aerobic exercises and to determine its effect on some respiratory indicators (forced Expiratory Volume in first Second Fev1, Peak Expiratory Flow PEF, and the Forced Vital Capacity FVC), and improve the respiratory functions to reduce the intensity and severity of asthma attacks for asthmatic children. This program was applied to a sample of 09 children with light to severe asthma and who are involved in the Asthma Association in Mostaganem. The application period lasted 20 weeks, with three training units per week. We relied on the experimental approach and used one group as a sample. Moreover we adopted pre and post measurements in addition to interstitial measurements at the end of each month using a Spirolab device. The results showed statistically significant differences between the pre and post measurement in the values ​​of respiratory indicators, in favor of the latter. This proves that aqua-aerobic exercises improve the function and efficiency of the respiratory system, and thus reduce the severity of asthma attacks for asthmatic children